23.1k views
4 votes
Write the equation of the function in vertex form, then convert to standard form.

Write the equation of the function in vertex form, then convert to standard form.-example-1
User Silvia
by
4.8k points

1 Answer

5 votes

The equation of the parabola in vertex form is


y=a(x-h)^2+k

where the point (h,k) is the coordinate of the vertex. From our picture, we can note that (h,k)=(-6,-4).

By substituting these values into our first equation, we have


y=a(x-(-6))^2-4

which gives


y=a(x+6)^2-4

Now, we can find the constant a by substituting one of the other given point. If we choose point (0,-2) into this last equation, we get


-2=a(0+6)^2-4

which gives


\begin{gathered} -2=a(6^2)-4 \\ -2=36a-4 \end{gathered}

then, by moving -4 to the left hand side, we have


\begin{gathered} -2+4=36a \\ 2=36a \\ or\text{ equivalently,} \\ 36a=2 \end{gathered}

and finally, a is equal to


\begin{gathered} a=(2)/(36) \\ a=(1)/(18) \end{gathered}

hence, the equation of the parabola in vertex form is


y=(1)/(18)(x+6)^2-4

Now, lets convert this equation into a standrd form. This can be done by expanding the quadratic term and collecting similar term. That is, by expanding the quadratic terms, we obtain


y=(1)/(18)(x^2+12x+36)-4

now, by distributing 1/18, we have


y=(1)/(18)x^2+(12)/(18)x+(36)/(18)-4

which is equivalent to


y=(1)/(18)x^2+(1)/(3)x+2-4

and finally, the parabola equation in standard form is


y=(1)/(18)x^2+(1)/(3)x-2

User Piotr Czapla
by
6.0k points